Attracting Sets Of Nonlinear Difference Equations With Time-Varying Delays - He, Danhua (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, a class of nonlinear difference equations with time-varying delays is considered. Based on a generalized discrete Halanay inequality, some sufficient conditions for the attracting set and the global asymptotic stability of the nonlinear difference equations with time-varying delays are obtained.